Histological remodelling of demineralised bone matrix allograft in posterolateral fusion of the spine – an ex vivo study - Bouaicha, Samy (BioMed Central, 2013)
BACKGROUND: Demineralised bone matrix (DBM) has shown to be effective in enhancing posterior fusion of the spine. Several animal studies and clinical investigations in humans showed its successful remodelling. The use of allogenic matrix may decrease the need of autologous bone graft and therefore helps prevent corresponding donor site morbidity. Since DBM products are very expensive, the question arises, whether it is completely remodelled into new bone, and therefore truly is comparable to autologous cancellous bone graft. To our knowledge there is no report of a consecutive series of patients where ex vivo histological analysis after postero-lateral fusion of the spine was performed. METHODS: Osseous biopsies of nine consecutive patients who underwent postero-lateral fusion of the spine for trauma were obtained at the time of elective removal of the hardware. Histological samples were then analyzed on ground and thin sections stained with toluidine blue and von Kossa stainings. RESULTS: Time span between index operation and removal of the metal ranged between 6 and 18 month. Histological analysis showed good incorporation and overall remodelling of DBM into new bone in all patients. No foreign body reaction was visible and new bone formation progressed time dependently with DBM in situ. Four out of nine patients showed more than 50% new bone formation after one year. CONCLUSION: DBM shows good overall remodelling properties in histological analysis and therefore seems to be an effective adjunct in postero-lateral fusion of the spine. Furthermore, DBM substitution increases over time.